2004
DOI: 10.1002/macp.200300104
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the Free Volume in Poly(styrene‐co‐acrylonitrile) from Positron Lifetime and Pressure Volume Temperature (PVT) Experiments

Abstract: Summary: The structure of the free volume and its temperature dependence between 25 and 190 °C of copolymers of styrene with acrylonitrile, SAN (0 to 50 mol‐% AN), is studied by pressure volume temperature (PVT) experiments and positron annihilation lifetime spectroscopy (PALS). In this second part of the work, PALS data are reported from which the temperature dependence of the mean size and size distribution of local free volumes (subnanometer size holes) is analysed. The mean hole volume, vh, varies in PS be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 82 publications
7
78
0
Order By: Relevance
“…Similar declination of σ 3 was observed also for an epoxy resin [11]. However, usually σ 3 at T k (or just below T k ) becomes a weakly increasing temperature function [7][8][9][10][12][13][14][15]. Values of τ 2 from 112 K up to T g seems to be constant (Fig.…”
Section: Three-distributed-component Analysissupporting
confidence: 77%
See 2 more Smart Citations
“…Similar declination of σ 3 was observed also for an epoxy resin [11]. However, usually σ 3 at T k (or just below T k ) becomes a weakly increasing temperature function [7][8][9][10][12][13][14][15]. Values of τ 2 from 112 K up to T g seems to be constant (Fig.…”
Section: Three-distributed-component Analysissupporting
confidence: 77%
“…Therefore a discrete-term analysis overestimates the values of τ 1 and I 1 . This approach was applied successfully in many works [7][8][9][10][11][12][13][14][15] to analysis of lifetime spectra for different polymeric and other molecular substances.…”
Section: J Kansymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses demonstrated that the predicted h=h(T) behavior at ambient pressure is correct (Yu et al 1994;Higuchi et al 1995;Srithawatpong et al 1999;Schmidt and Maurer 2000;Schmidt 2000;Olson et al 2002;Olson 2004;Dlubek et al 2004Dlubek et al , 2006Consolati et al 2005). Assuming that at T≈T g +2 0t o2 5°Ch=f PALS , superposed the two sets of data in full range of temperature.…”
Section: Comparison Of Free Volumes From Pals and Pvtmentioning
confidence: 95%
“…Documented dependence of I 3 on other factors than free volume fraction (Schmidt 2000), distance form T g (Kisliuk et al 2000), and the void geometry (Consolati et al 2005) may be a reason for this variability. Another approach was proposed by Dlubek et al (1998Dlubek et al ( , 2004Dlubek et al ( -2006. The authors calculated free volume cell size from Eq.…”
Section: Application Of S-s Theory To Palsmentioning
confidence: 99%